Exclusion by design: The undocumented 1.5 generation in the U.S - Sanchez, Linda E. (Frontiers in Sociology, 2023)
This article focuses on Mexican individuals who grew up in the U.S. (1.5 generation) without documents and were not able to benefit from Deferred Action for Childhood Arrivals (DACA) or who were unable to renew their DACA. A 2012 Executive Action by former president Obama, DACA gave some undocumented youth relief from deportation and a 2-year renewable work permit provided they met certain criteria. Undocumented individuals DACA failed to reach have generally been overlooked in immigration research in favor of examining how DACA recipients’ lives have been transformed by DACA. This project helps fill this gap by examining life outside of DACA, and how the program acted as an internal U.S. border of exclusion for many. This research also aids in understanding the impacts of changing government policies on vulnerable populations, especially those who are in some respects made even more vulnerable by their faith in the government, fear of the government, or are actively excluded from government programs. This investigation is part of a study that compares 20 DACA beneficiaries to 20 individuals without DACA. Through ethnographic methodologies and one-on-one interviews, this article examines the 20 research participants who fall outside DACA. It investigates why people who qualified for DACA did not apply, barriers to applying/renewing, and how members of the 1.5 generation were excluded from the program by restrictions such as date of arrival requirements. The article discusses what it means for research participants to live outside of DACA, and how they see their lives because they do not have DACA while others do. For example, what does it mean to age out of qualifying for DACA? What actions did individuals then take regarding their lack of legal status?